Bedside healthcare rationing dilemmas: A survey from Portugal. - Pinho, Micaela (2016)
Purpose – The purpose of this paper is to seek to elicit, in a context of economic crisis, the social preferences for the microallocation of scarce healthcare resources. Design/methodology/approach – Data were collected from an online questionnaire which includes a hypothetical rationing choice scenario with four patients differentiated by their personal characteristics and health states competing for treatments and a set of statements that embodies: distributive criteria for prioritizing patients; the authorship of these types of decisions; and the likelihood of these decisions to be taken. Descriptive statistics, factor analysis and non-parametric test were used for describing and validating the data. Findings – Findings suggest that respondents: support a pluralism of distributive principles in prioritizing patients with an incident in utilitarianism and the reducing of inequalities in health, translated in the fair-inning and in emotional arguments of fragility; trust in the health professional to make prioritization decisions; and are conscious that rationing decisions will be real in the short term. Practical implications – The pursuit of efficiency and the equalizing of a lifetime health seem to be the criteria that should guide any rationing policy at the micro level. Originality/value – This study addresses simultaneously several ethical principles inherent to microallocation healthcare resources in a suitable context in which Portugal is facing an economic crisis and where, consequently, rationing healthcare policies gain prominence on the political agenda.